Deep Learning for Crowd Counting: A Survey - Tjeng Wawan Cenggoro (Bina Nusantara University, 2019)
The growth of deep learning for crowd counting is immense in the recent years. This results in numerous deep learning model developed with huge multifariousness. This paper aims to capture a big picture of existing deep learning models for crowd counting. Hence, the development of novel models for future works can be accelerated.